Analisis Pengaruh Environmental, Social, and Governance (ESG) Terhadap Sustainable Development Goals (SDGs) Pada UMKM - Sinaga, Klemensia Erna Christina; Damayanti (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) practices on the achievement of the Sustainable Development Goals (SDGs) in Micro, Small, and Medium Enterprises (MSMEs) in Bandar Lampung. ESG is considered a strategic framework that promotes sustainable business practices aligned with global development goals. Primary data were collected through the distribution of questionnaires to 30 MSME entrepreneurs. Data analysis was conducted using simple linear regression. The results indicate that ESG disclosure has a positive effect on the achievement of SDGs among MSMEs with a significance value of 0.006 and an R Square of 0.238. These findings suggest that implementing ESG can serve as an essential strategy in promoting sustainable empowerment of MSMEs. The population in this study consisted of MSMEs in Bandar Lampung. The type of data used was primary data, obtained from 30 questionnaires distributed to MSME business owners. The sampling technique used was total population sampling. Data were analyzed using simple linear regression. The results show that ESG has a positive effect on SDG achievement.